2013
DOI: 10.1097/ccm.0b013e318265792b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rescue Breathing During Cardiopulmonary Resuscitation on Lung Function After Restoration of Spontaneous Circulation in a Porcine Model of Prolonged Cardiac Arrest*

Abstract: Appropriate rescue breathing during cardiopulmonary resuscitation does not influence the prognosis of cardiac arrest or the hemodynamics after restoration of spontaneous circulation but can improve lung function and alleviate lung injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 23 publications
1
13
1
Order By: Relevance
“…Data of the lung function of patients with PTE have been ongoing for a long time[192021] and also the data of heart arrest. [2223] However, the study about CPR with thrombolysis of CA caused by PTE was reported rarely. Based on this, we performed CPR with thrombolysis in a CA porcine model caused by PTE to investigate the success rate of ROSC, short-time survival rate, and the pulmonary function variations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data of the lung function of patients with PTE have been ongoing for a long time[192021] and also the data of heart arrest. [2223] However, the study about CPR with thrombolysis of CA caused by PTE was reported rarely. Based on this, we performed CPR with thrombolysis in a CA porcine model caused by PTE to investigate the success rate of ROSC, short-time survival rate, and the pulmonary function variations.…”
Section: Discussionmentioning
confidence: 99%
“…The Raw was a transient increase which was different from CA model caused by ventricular fibrillation. [22] It may attribute to platelet aggregation, endothelial cell injury, release of inflammatory mediators such as serotonin, histamine, bradykinin, platelet activating factor, and endothelin which could cause bronchial smooth muscle contraction. The EVLWI and PVPI are predicators for the acute lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…High-impulse CPR with its high-velocity short duration compression phase and longer duration decompression phase (or duty cycle adequately < 50%) not only produces superior hemodynamics but also apparently produces substantial compression-induced ventilation when the airway is unobstructed (i.e, when intubated) [3,4,5].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…it requires at least 50 mm [3] or more depending on the size of the chest for the displacement of A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT enough air adequately above dead space. Complete recoil cannot be achieved when performing effective-depth chest compressions at a 100/min rate, 50-mm compression depth and 50% duty cycle (or without high-impulse CPR) [9].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In a pig model experimental study, CPR with continuous compression cause the increase of EVLW, lung injury score and resistance comparing with the 30:2 compression/rescue ventilation CPR group but not affect the prognosis and hemodynamic after CPR [17].…”
Section: Ventilation During Cprmentioning
confidence: 99%